2016
DOI: 10.5551/jat.31526
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status is Associated with Inflammation and Predicts a Poor Outcome in Patients with Chronic Heart Failure

Abstract: These data indicate that a poor nutritional status as assessed using the CONUT score and atherosclerosis as indicated by CIMT is significantly associated with inflammation and predicts poor outcomes in patients with CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 41 publications
4
81
0
Order By: Relevance
“…Nakagomi et al also found that malnutrition correlated with inflammation and atherosclerosis in patients with chronic heart failure and was associated with worse clinical outcomes. 37 In the present study, patients with low serum in the model with both serum albumin and hs-CRP, even compared with the models with serum albumin alone and with hs-CRP alone.…”
Section: Discrimination and Reclassification Of Serum Albumin And Hs-crpmentioning
confidence: 97%
“…Nakagomi et al also found that malnutrition correlated with inflammation and atherosclerosis in patients with chronic heart failure and was associated with worse clinical outcomes. 37 In the present study, patients with low serum in the model with both serum albumin and hs-CRP, even compared with the models with serum albumin alone and with hs-CRP alone.…”
Section: Discrimination and Reclassification Of Serum Albumin And Hs-crpmentioning
confidence: 97%
“…7,50 Moreover, low S-Alb and congestive heart failure may promote intestinal edema 51 and disturb the absorption of essential nutrients such as antioxidative vitamins and oligoelements. 52 Altogether these factors contribute to the dangerous combination of persistent inflammation and lower S-Alb concentrations that is statistically and probably also causally linked to the extremely high cardiovascular burden and mortality in ESRD. 53 The observed associations-albeit strong-may be underestimated when analyses are based on single measurements of S-Alb and CRP.…”
Section: Sarcopeniamentioning
confidence: 99%
“…Inflammatory cytokines promote PEW by acting directly on the gastrointestinal system or indirectly through affecting appetite and resting energy expenditure . Moreover, low S‐Alb and congestive heart failure may promote intestinal edema and disturb the absorption of essential nutrients such as antioxidative vitamins and oligoelements …”
mentioning
confidence: 99%
“…The association between malnutrition and inflammation has been shown in patients with chronic kidney disese and chronic heart failure 24,25 . Based on the current evidence, inflammation can play a crucial role in the development of atherosclerotic plaques in the epicardial coronary arteries and microvascular circulation of the heart 9.10 .…”
Section: Discussionmentioning
confidence: 99%